PERANCANGAN APLIKASI E-MODUL PEMBELAJARAN INFORMATIKA DI MTS NEGERI 6 AGAM - Putra, Yudhi Permana; Musril, Hari Antoni (Jurnal Edukasi Elektro, 2022)
ABSTRACT:In its implementation, motivated by the need for an e-module learning media that is more interesting, one that can be utilized is the application of electronic modules (e-modules). E-modules can be made with various applications, one of which is the sigil application. Components are made to make it easier for students to understand learning with the features that exist in the application, besides that in solving existing problems students can also see the steps on how to complete the exercises and assignments. The research method used is the Research and Development (R&D) research method. The system development model uses the System Development Life Cycle (SDLC) by applying the development model (Luther Sutopo). The results of the validity test conducted by computer experts showed that this product with a value of 0.82 was very good. The results of the practicality test conducted by the informatics subject teacher of this product were declared very practical, the value of 0.86 was very practical. And the results of the effectiveness test carried out with a value of 0.86 are very good.ABSTRAK:Dalam pelaksanaannya, dilatar belakangi oleh perlu adanya sebuah media pembelajaran e-modul yang lebih menarik, Salah satu yang bisa dimanfaatkan adalah penerapan electronic modul (e-modul). E-modul dapat dibuat dengan berbagai macam aplikasi, salah satunya aplikasi sigil. Komponen yang dibuat untuk mempermudah siswa dalam memahami pembelajaran dengan fitur-fitur yang ada pada aplikasi tersebut, selain itu dalam menyelesaikan permasalahan yang ada siswa juga bisa melihat langkah-langkah bagaimana menyelesaikan latihan dan tugas yang dikerjakan. Metode penelitian yang digunakan adalah metode penelitian Research and Development (R&D). Model pengembangan sistemnya menggunakan System Development Life Cycle (SDLC) dengan menerapkan model pengembangan (Luther Sutopo). Hasil uji validitas yang dilakukan oleh ahli komputer menunjukkan produk ini dengan nilai 0,82 sangat baik. Hasil uji praktikalitas yang dilakukan oleh guru mata pelajaran informatika produk ini dinyatakan sangat praktis nilai 0,86 sangat praktis. Dan hasil uji efektifitas yang dilakukan dengan dengan nilai 0,86 sangat baik.